Ocular Refraction at Birth and Its Development During the First Year of Life in a Large Cohort of Babies in a Single Center in Northern Italy - Semeraro, Francesco; Forbice, Eliana; Nascimbeni, Giuseppe; Cillino, Salvatore; Bonfiglio, Vincenza Maria Elena; Filippelli, Maria Elena; Bartollino, Silvia; Costagliola, Ciro (Frontiers in Pediatrics, 2020)
ABSTRACT The purpose of this study has been to investigate refraction at birth and during the first year of life in a large cohort of babies born in a single center in Northern Italy and to analyze refractive errors in relation to the gestational age at birth. An observational ophthalmological assessment was performed within 24 h of birth to 12,427 newborns. Refraction was examined using streak retinoscopy, after administration of tropicamide (1%). Values between +0.50 ≤ D ≤ +4.00 were defined as physiological refraction at birth. Newborns out of physiological refraction were followed up during the first year of life. Comparative analyses were conducted in a subgroup of babies with known gestational age. The following distribution of refraction at birth was recorded: 88.03% of the babies, physiological refraction; 5.03% moderate hyperopia; 2.14%, severe hyperopia; 3.4%, emmetropia; 0.45%, myopia; 0.94%, astigmatism; and 0.01%, anisometropia. By the first year of life, a reduction of hyperopia and astigmatism, and stabilization of myopia were observed. Preterm babies had a four times higher risk of congenital myopia and a three times higher risk of congenital emmetropia as compared to term babies. Conclusions: Data obtained at birth changed during the first year of life, leading to a normalization of the refraction values. Gestational age at birth affects the incidence of refractive errors and amblyopia.